Effect of exercise intensity on biathlon standing shooting performance and rifle movement during outdoor roller skiing - Danielsen, J.; Luchsinger, H.; Ravndal, A.; Laaksonen, M. S.; Sandbakk, Ø.; McGhie, D. (Medicine & Science in Sports & Exercise, 2025)
Purpose The objective of this study is to investigate the effect of exercise intensity on standing shooting performance and related technical variables in elite biathletes performing roller skiing and live shooting outdoors.